Anatomical and Molecular Responses of Soy Bean (Glycine Max (L.) Merr.) Due to Salinity Stresses - Juwarno Juwarno; Siti Samiyarsih (Universitas Jenderal Soedirman, 2017)
Current study was aimed to explore both anatomical and molecular responses of 3 soy bean cultivars (Mahameru, Slamet and Detam) which was given salinity stress. Data of the Mahameru cultivar showed that the widest stomata on upper epiderm 11.38 µm, the thickest upper epiderm was 10.71µm, but the thickest of lower epiderm was only 9.98 µm, the highest density of stomata on lower epiderm was 13.66 per mm2 leaf area, and the thickest mesophyll was 110.37 µm. Molecular marker applying OPA-2 primer with RAPD technique showed the Detam and Slamet cultivars were having different bands one to each other even with the Mahameru cultivar. While the application of OPA-4 primer with the same technique showed there were no genetically different on Mahameru cultivar between control and treatment 80 mM NaCl. The OPA-8 primer showed that the control block of Slamet cultivar was different from either control block of others as well as treatment block of 80 mM NaCl. The use of OPA-18 primer showed that the Slamet cultivar of the control block and so its 80 mM NaCl block was different from Detam and Mahameru, where the 500th base of Slamet cultivar did not have DNA band.